A general method of Suzuki–Miyaura cross-coupling of 4- and 5-halo-1, 2, 3-triazoles in water. Issue 45 (8th November 2017) - Gribanov, Pavel S.; Chesnokov, Gleb A.; Topchiy, Maxim A.; Asachenko, Andrey F.; Nechaev, Mikhail S.
Abstract : A general method of the synthesis of 1, 4, 5-trisubstituted-1, 2, 3-triazoles by Suzuki–Miyaura cross-coupling from 4- and 5-halo-1, 2, 3-triazoles. Abstract : A general method of the synthesis of 1, 4, 5-trisubstituted-1, 2, 3-triazoles by Suzuki–Miyaura cross-coupling from 4- and 5-halo-1, 2, 3-triazoles is reported. The reaction is mediated by an expanded-ring N-heterocyclic carbene palladium complex in water. The developed reaction protocol meets the requirements of "green chemistry". Cross-coupling of 4- and 5-chlorotriazoles is reported for the first time.